Contemporary Art in Galicia: Artists, Art Galleries and Women Who Manage Them - Villaverde Solar, María Dolores (Madrygal. Revista de Estudios Gallegos, 2015)
This paper will summarize art in Galicia from the eighties, a time in which women were not excluded from the artistic world, to the present moment. We shall analyse women’s situation in contemporary art and the role they played. We shall study not only artists but also gallery owners and museum directors, as in this period women were not solely limited to being artists or models. Following this same line, we shall see if feminist art is still alive and present in contemporary art centres.